Borders and Crime
XIV, 202 p.
Keywords: The collection considers the growing importance of the border as a prime site for criminal justice activity and explores the impact of border policing on human rights and global justice. It covers a range of subjects from e-trafficking, child soldiers, the 'global war on terror' in Africa and police activities that generate crime.